A mitochondrial phylogeny uncovers taxonomic ambiguity and complex phylogeographic patterns in the eastern Australian land snail Austrochloritis (Stylommatophora, Camaenidae). (6th January 2020) - Köhler, Frank; Criscione, Francesco; Shea, Michael
Abstract: We analyzed the mitochondrial differentiation of the southeast Australian land snail genus Austrochloritis Pilsbry, 1890, family Camaenidae, which encompasses 34 currently accepted species. These species were exclusively described and delimited based on comparative shell morphology, while their reproductive anatomy has remained undocumented. Phylogenetic analyses of partial fragments of the cytochrome c oxidase subunit 1 gene ( COI ) and 16S rRNA ( 16S ) genes revealed widespread incongruence between the shell‐based species taxonomy and the branching patterns of phylogenetic trees indicating the urgent need of more comprehensive systematic review. The phylogeographic patterns in Austrochloritis are consistent with well‐documented biogeographic barriers in southeastern Australia, namely the Hunter River Valley and the McPherson Range, which demarcate concomitant biogeographic breaks in the biota of the region. These breaks are thought to result from past expansions and contractions of mesic forests caused by the climatic oscillations during the mid to late Neogene. Our study also provides evidence for potentially widespread sympatry of Austrochloritis species in the northern part of their distribution, which is in conflict with contemporary paradigms that presume predominantly allopatric distributions in congeneric land snails in eastern Australia. Abstract : Phylogeographic patterns Austrochloritis land snails along the SE coast of Australia are shaped by two biogeographic barriers, the Hunter River and McPherson Range, which demarcate concomitant biogeographic breaks in the biota of the region. These breaks are thought to result from past expansions and contractions of mesic forests due to Neogene climatic oscillations. North of the Hunter, widespread sympatry of Austrochloritis clades is in conflict with contemporary paradigms that presume predominantly allopatric distributions in congeneric Australian land snails.